Chronic Tenosynovitis Caused by Mycobacterium terrae: A Case Report Highlighting a Diagnostic Challenge - Alex Giannini; Pietro Antonini (Annals of Internal Medicine: Clinical Cases)
We report a rare case of chronic tenosynovitis of the upper extremity caused by Mycobacterium terrae, an infrequent and underdiagnosed pathogen. A 64-year-old man presented with persistent pain and swelling in the hand following a minor puncture wound. Despite multiple empirical treatments, including corticosteroids, antibiotics, and antifungals, the condition progressed over several months (Figure 1). Surgical intervention, histopathologic examination revealing granulomatous inflammation, and prolonged microbiological culture ultimately identified M terrae. Susceptibility-guided antimicrobial therapy resulted in complete clinical resolution. This case highlights the diagnostic complexity of M terrae infections and emphasizes the importance of considering atypical pathogens in cases of chronic tenosynovitis, especially when conventional therapies fail.